The famine that wasn't? 1799-1801 in Ireland - Liam Kennedy; Peter M. Solar (Queen's University Centre for Economic History (QUCEH), 2019)
Strange Times. There were back-to-back harvest failures in 1799-1800, coming fast on the heels of the insurrections of 1798. The result was massive and sustained inflation in food prices. The conundrum is why there was so little excess mortality. Our approach is to begin by discussing the harvest failures of 1799 and 1800, drawing some implications from the price movements of foodstuffs in Ireland and Britain. We then present evidence from our limited sample of parish registers that suggests that excess mortality was probably quite limited, as was the check to births. A further striking feature of the period, and hardly unrelated, was the role of the state. Though heavily absorbed with the "high politics" of the Union, politicians and policy makers took swift and determined action to stave off distress and public disorder. The range and effectiveness of these measures are assessed. We draw attention to a variety of local initiatives to grapple with problems of food scarcity and lack of purchasing power and offer an analytical sketch as to how the relationship between farmers and labourers might have shaped the outcome of the crisis in the countryside. The concluding section reflects on methods of calculating the impact of state-sponsored famine relief - the lives saved in a sense - and argues that a dynamic rather than a static approach is what is required. And second, the limitations of inflated food prices as indicators of famine conditions, at least under certain forms of peasant agriculture, are laid bare. These two sets of argument help unlock the conundrum as to why excess mortality did not give rise to mass mortality under environmental conditions as unpropitious as those of 1800- 01. There may be implications here for the understanding of food crises in rural societies with large subsistence sectors elsewhere in the pre-industrial world.
Keywords: N33; N54; N94; 330